Optimalisasi Peran Masyarakat dan UMKM Dalam Bidang Ekonomi dan Kesehatan Pada Masa Pandemi di Karangnongko, Plosoklaten, Kediri - M. Dimyati Huda; Mariyatul Qibtiyah (Abdimas Indonesian Journal, 2022)
The role of the community during the Covid-19 pandemic is very important in minimizing or reducing and breaking the chain of the spread of Covid-19. Many people only know about social distancing, physical distancing, always wearing a mask when going out of the house, always washing their hands after doing activities from outside. However, it turns out that the community has not yet understood this, because it is still difficult to get used to or teach people to live clean and healthy. And MSMEs themselves are businesses that can improve the community's economy, but due to the Covid-19 pandemic, MSMEs have experienced difficulties and decreased sales. This research method uses the method of observation, observation is a method of collecting data by observing directly or going into the field. By observing directly the community and MSMEs in Karangnongko Hamlet. Looking at the existing problems, the IAIN Kediri 2021 KKN (Real Work Lecture) activity program will be carried out by increasing public knowledge and public awareness in Karangnongko Hamlet about the dangers of covid and the efforts made to prevent the spread of the Covid-19 outbreak, making community learning to live clean and healthy. Knowing how to overcome the decline in MSMEs in Karangnongko Hamlet by using social media and digital possibilities that can help restore MSMEs in Karangnongko Hamlet.